DIANA-miRGen v3.0: accurate characterization of microRNA promoters and their regulators. Issue Volume 44:Issue D1(2016) (19th November 2015) - Georgakilas, Georgios; Vlachos, Ioannis S.; Zagganas, Konstantinos; Vergoulis, Thanasis; Paraskevopoulou, Maria D.; Kanellos, Ilias; Tsanakas, Panayiotis; Dellis, Dimitris; Fevgas, Athanasios; Dalamagas, Theodore; Hatzigeorgiou, Artemis G.
Abstract: microRNAs (miRNAs) are small non-coding RNAs that actively fine-tune gene expression. The accurate characterization of the mechanisms underlying miRNA transcription regulation will further expand our knowledge regarding their implication in homeostatic and pathobiological networks. Aim of DIANA-miRGen v3.0 (http://www.microrna.gr/mirgen ) is to provide for the first time accurate cell-line-specific miRNA gene transcription start sites (TSSs), coupled with genome-wide maps of transcription factor (TF) binding sites in order to unveil the mechanisms of miRNA transcription regulation. To this end, more than 7.3 billion RNA-, ChIP- and DNase-Seq next generation sequencing reads were analyzed/assembled and combined with state-of-the-art miRNA TSS prediction and TF binding site identification algorithms. The new database schema and web interface facilitates user interaction, provides advanced queries and innate connection with other DIANA resources for miRNA target identification and pathway analysis. The database currently supports 276 miRNA TSSs that correspond to 428 precursors and >19M binding sites of 202 TFs on a genome-wide scale in nine cell-lines and six tissues of Homo sapiens and Mus musculus .